Racial and Ethnic Disparities in Maternity Care in the United States Put Mothers and Babies at Risk. Issue 5 (September 2018) - Simpson, Kathleen Rice
Abstract : There are dramatic differences in maternal and infant outcomes among racial and ethnic groups in the United States. Some of these disparities are due to inequitable maternity care. Potential underlying causes and solutions are discussed.